Analisis Intensitas Cahaya di Dalam Ruangan dengan Menggunakan Aplikasi Smart Luxmeter Berbasis Android - Sheika Ika Putri; Sudarti Sudarti (Jurnal Materi dan Pembelajaran Fisika, 2022)
The lighting system is very important to pay attention to because our eye health will be disturbed by the lack of light intensity. A room, especially a workspace, must have adequate light following predetermined standards. Analysis of light intensity measurement using a digital lux meter to determine the value of light intensity, this experiment was conducted to determine whether the light intensity in the room had or did not meet the standard of SNI 16-7062-2004. The digital lux meter used can measure the light intensity generated from the room prepared using 3-watt LED lights with a room size of 3 × 3 meters. Data retrieval has been done by placing a lux meter in every corner of the room at the same distance between the light source and the lux meter, which is 2 meters. To determine the effectiveness of the light intensity, the measurement results are compared with SNI's lux meter. The experimental data that have been carried out do not meet the SNI requirements for lighting in the workspace, the average intensity value is 12.25 Lux, 153 lumens in 15 seconds uses a calibration of 100%.